SEM and FT-IR Studies on Nature of Adsorption of Mercury(II) and Chromium(VI) from Wastewater using Chemically Activated Syzygium jambolanum Nut Carbon - Muthukumaran, K.; Sophie Beulah, S. (Asian Journal of Chemistry, 2010)
The chemically activated carbon prepared from Syzygium jambolanum nut [CHSJC], an agricultural waste, after activation with ammonium persulphate, an oxidizing chemical in the presence of sulphuric acid followed by thermal activation by modified dolomite process was successfully used to remove mercury(II) and chromium(VI) from wastewater in batch studies by adsorption process. Surface morphology of the carbon was analyzed by scanning electron microscope (SEM) before and after the adsorption of Hg(II) and Cr(VI) and the results revealed the presence of micropores which are responsible for adsorption. Fourier transform infrared (FT-IR) spectroscopic studies of the carbon showed that physio-sorption took place on the surface of the carbon and the functional groups responsible for adsorption. SEM and FT-IR analysis of high temperature activated Syzygium jambolanum nut carbon [HSJC] and a commercial activated carbon (CAC) before and after the adsorption of Hg(II) and Cr(VI) were also carried out for comparison purposes.